Toward the Development of tES- Based Telemedicine System: Insights From the Digital Transformation and Neurophysiological Evidence - Ikeda, Takashi; Nishida, Keiichiro; Yoshimura, Masafumi; Ishii, Ryouhei; Tsukuda, Banri; Bunai, Tomoyasu; Ouchi, Yasuomi; Kikuchi, Mitsuru (Frontiers in Psychiatry, 2022)
no abstract (due to Opinion style)